A novel AgNPs/MOF substrate-based SERS sensor for high-sensitive on-site detection of wheat gluten - Linglin Fu; Yanzhuo Du; Jinru Zhou; Huan Li; Minzi Wang; Yanbo Wang (Food Science and Human Wellness)
Gluten, known as the major allergen in wheat, has gained increasing concerns in industrialized countries, resulting in an urgent need for accurate, high-sensitive, and on-site detection of wheat gluten in complex food systems. Herein, we proposed a silver nanoparticles (AgNPs)/metal-organic framework (MOF) substrate-based surface-enhanced Raman scattering (SERS) sensor for the high-sensitive on-site detection of wheat gluten. The detection occurred on the newly in-situ synthesized AgNPs/MOF-modified SERS substrate, providing an enhancement factor (EF) of 1.89 × 105. Benefitting from the signal amplification function of AgNPs/MOF and the superiority of SERS, this sensor represented high sensitivity performance and a wide detection range from 1 × 10-15 mol/L to 2 × 10-6 mol/L with a detection limit of 1.16 × 10-16 mol/L, which allowed monitoring the trace of wheat gluten in complex food system without matrix interference. This reliable sandwich SERS sensor may provide a promising platform for high-sensitive, accurate, and on-site detection of allergens in the field of food safety.